2022
DOI: 10.1177/23259671221092733
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Extensor Carpi Radialis Brevis Tenotomy and Debridement Versus Debridement Alone for Refractory Lateral Epicondylitis: Clinical and MRI Evaluation

Abstract: Background: Arthroscopic debridement of the extensor carpi radialis brevis (ECRB) tendon is a widely accepted procedure used in refractory lateral epicondylitis. However, residual pain occurs in some patients. Purpose: To investigate the clinical effectiveness of arthroscopic extended debridement (ECRB tenotomy and debridement) in the treatment of lateral epicondylitis. Study Design: Cohort study; Level of evidence, 3. Methods: Patients with refractory lateral epicondylitis were consecutively recruited for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Although comparative studies have shown similar long-term results, arthroscopically treated patients experience enhanced early postoperative pain relief, as well as hastened return-to-work times. 2 …”
mentioning
confidence: 99%